Fine‐grained 3C‐SiC thick films prepared via hybrid laser chemical vapor deposition. Issue 9 (30th March 2019) - Lai, Youfeng; Cheng, Hong; Jia, Zhenglin; Li, Qizhong; Yang, Meijun; Zhang, Song; Han, Mingxu; Tu, Rong; Goto, Takashi; Zhang, Lianmeng
Abstract: An ultraviolet laser (λ = 266 nm) operated in pulsed mode and a diode laser (λ = 1060 nm) operated in continuous mode were simultaneously applied to create a hybrid laser chemical vapor deposition (CVD) approach. Fine‐grained 3C‐SiC thick films were prepared via hybrid laser CVD by using SiCl4, CH4 and H2 as precursors. The effects of the ultraviolet laser on the preferred orientations, microstructures, microhardness values and deposition rates of 3C‐SiC thick films were investigated. The 3C‐SiC thick films that were prepared at 4 kPa via diode laser CVD exhibited <110>‐orientations and 5‐100 µm grain sizes, whereas those prepared via hybrid laser CVD were randomly oriented with 0.5‐5 µm grain sizes. Compared to diode laser CVD, the additional irradiation of the ultraviolet laser in the hybrid laser CVD improved the Vickers microhardness values of the 3C‐SiC thick films from 30 to 35 GPa, and the maximum deposition rate was also increased from 935 to 1230 µm/h.